ENTRE PALAVRAS, LAÇOS E REDES: UMA LEITURA DE POLÊMICAS E CENSURAS À LITERATURA INFANTIL NO BRASIL CONTEMPORÂNEO, SUSCITADAS A PARTIR DAS REDES SOCIAIS - Melo, Fabiana Monnerat de (2020)
It is related to a comprehensive study of the contemporary controversies (during the simultaneous and subsequent period of the Judicial-Mediatic-Parliamentary strike of 2016, in Brazil) involving infantile literature; the outline focuses particularly in c